Do Cognitive Interview Instructions Contribute to False Beliefs and Memories?. Issue 1 (8th August 2012) - Sharman, Stefanie J.; Powell, Martine B.
Abstract: To examine whether exposing people to false events using instructions taken from the cognitive interview creates false beliefs and false memories, we conducted an experiment where participants took part in two sessions. First, they rated how confident they were that they had experienced certain childhood events and their memories of those events; they also rated how plausible they thought the events were. Second, 2 weeks later, participants were exposed to two of three false target events: one high, one moderate, and one low plausibility. For the first event, participants were instructed to either report everything or mentally reinstate the event context. For the second event, participants received both instructions. The third event was the control event about which participants received no instructions. Finally, participants rated their confidence and memories the second time. The results showed that the cognitive interview instructions had little to no effect on the development of false beliefs and false memories. Copyright © 2012 John Wiley & Sons, Ltd.